Characterization of Nanostructured Allophane Clays and Their Use as Support of Iron Species in a Heterogeneous Electro-Fenton System - Ureta-Zanartu, M; Garrido-Ramirez, E (Elsevier Ltd, 2013)
Nanostructured allophane clays supported with iron oxide (AlSi2Fe6) were characterized by X-ray photoelectron spectroscopy (XPS) and Mössbauer spectroscopy showing the presence of both Fe3 + and Fe2 + species on the allophane surface. A glassy carbon disk (GC) modified with a film obtained by the deposition of drops of a dispersion formed by graphite and AlSi2Fe6 in water was used as working electrode in a heterogeneous electro-Fenton system (HE-Fenton) for the oxidation of atrazine. The effect of the initial pHs and the proportion of AlSi2Fe6/graphite in the mixture were studied and compared with the heterogeneous Fenton process. The HE-Fenton system using AlSi2Fe6-GC electrodes showed higher efficiency towards the oxidation of atrazine than the heterogeneous Fenton one; mainly due to the continuous and simultaneous electro-regeneration of iron species (Fe3 +/Fe2 +) and electro-generation of hydrogen peroxide by the oxygen reduction process. The degradation of atrazine in this HE-Fenton system reached almost 100% at pH 3.0 after 8 h, whereas at more neutral pH (~ 6) a 76% of degradation was obtained. Two reaction products were identified by HPLC: desethyl-atrazine (DEA) and desethyl-desisopropyl-atrazine (DEIA). © 2013 Elsevier B.V.